Developing an Army strategy for building partner capacity for stability operations - Marquis, Jefferson P. (Rand Corporation monograph series., 2010)
The U.S. government is facing the dual challenge of building its own interagency capacity for conducting stability operations while simultaneously building partner capacity (BPC) for stability operations. The purpose of this study is to assist the U.S. Army, the Department of Defense, and other U.S. government agencies in developing an integrated BPC for stability operations strategy. To accomplish this goal, a RAND Arroyo Center study team conducted an exploratory analysis of key strategic elements within the context of BPC and stability operations guidance as well as ongoing security cooperation programs, using a variety of analytical techniques. In general, this study concludes that BPC and stability operations are receiving a good deal of attention in official strategy and planning documents. However, insufficient attention is being paid to the details of an integrated strategy. A baseline analysis of existing security cooperation programs needs to be undertaken to comprehend the type, scope, and target of activities related to BPC for stability operations. An assessment of these activities should then be conducted, focusing on both process outputs and operational outcomes. In addition, the Departments of State and Defense should develop a rigorous method for selecting and prioritizing partners whose stability operations capacity they wish to build. Ideally, the results of these analytical processes will have a significant impact on the set of BPC for stability operations activities and partners, aligning relevant and effective activities with appropriate partners.